Sosialisasi Kepastian Hukum Sertifikat Elektronik Sebagai Bukti Hak Atas Tanah di Desa Pangkalan Baru, Kecamatan Siak Hulu, Kabupaten Kampar - Sri Arlina; Mira Hafizah Tanjung; Anggraini Dwi Milandry; Evi Yanti (I-Com: Indonesian Community Journal, 2025)
Pangkalan Baru Village as a partner faces various problems including the low understanding of the partner village community regarding the legal basis governing land, especially regarding the development of land registration rules in Indonesia, the Community Service Team found a phenomenon that the partner community did not know exactly how to resolve land disputes in the realm of criminal law both online and offline. Based on this phenomenon, the PKM Team provided legal counseling related to the Socialization of Legal Certainty of Electronic Certificates as Proof of Land Rights in Pangkalan Baru Village, Siak Hulu District, Kampar Regency. The method used by doing various stages, namely the pre-survey stage, the preparation stage, the socialization stage and finally the evaluation stage. After being given socialization related to various phenomena that partner communities face, partner communities now understand well related to the legal certainty of electronic certificates as evidence of land rights.